The effect of neonicotinoids on bumblebees (Bombus spp.): a systematic review - Dennis, Daisy J.; Gibbs, Alexandra J. (Frontiers in Bee Science, 2025)
Neonicotinoids are systemic insecticides used in agriculture to control herbivorous pests by targeting the nervous system. However, the persistence and presence of neonicotinoids in pollen and nectar raises concerns regarding impacts on non-target organisms, particularly pollinators such as bees. Bumblebees (Bombus spp.) are essential for wild plant pollination and crop production but are vulnerable to insecticides due to their foraging behaviors and ecological traits. While commercially available forms of neonicotinoids have been banned in select countries over recent years, they are still utilized extensively in many parts of the world, with limited understanding of impacts on bumblebee physiology and behavior. To investigate neonicotinoid effects on bumblebees, we systematically reviewed studies from Scopus and Web of Science following PRISMA 2020 guidelines. A total of 52 primary studies were identified, revealing a pronounced geographic bias, with 81% of research conducted in the UK and the U.S. (54% and 27%, respectively). Bombus terrestris, B. terrestris audax, and B. impatiens emerged as the most studied species whereas imidacloprid, thiamethoxam, and clothianidin were the most common neonicotinoid compounds tested, represented in 88% of the studies. In comparison, only a single study performed on B. ephippiatus and there are currently no published studies assessing the impact of the compounds nitenpyram or dinotefuran on bumblebee health and behavior. Behavioral alterations, particularly foraging and cognition, were the most prevalent reported effects of neonicotinoids, followed by reproductive health and physiological impacts. This review highlights the need for more geographically and taxonomically diverse research, particularly in regions still using neonicotinoids. The prevalence of sublethal effects raises concerns for colony health and pollination services, yet direct assessments of pollination efficiency remain limited. As such, critical knowledge gaps remain, particularly regarding understudied neonicotinoid compounds and bumblebee species, emphasizing the need for further research to inform sustainable agricultural practices and conservation strategies.